Prioritizing Shipyard Conversion Requirements Regarding Green Ship and Green Shipyard Concept - Koray, Murat (Transactions on Maritime Science, 2023)
The zero waste, zero emission targets set by the International Maritime Organization (IMO) regarding ship emissions until 2070 brought the realization of the green ship and green shipyard concept to the fore. Shipyards around the world are predominantly second and third generation. The fourth and fifth-generation shipyards do not fully meet the 2070 criteria. Therefore, it is necessary to build green shipyards or transform existing shipyards to produce green ships. The study aims to determine the shipyards' conversion requirements and prioritize these needs so that a 32.000 DWT Dry Bulk Carrier can be built and classified as a green ship. Qualitative research methods were used in the study, and the criteria determined in this context are analyzed with the Analytical Hierarchy Process (AHP). At the end of the study, the proposals regarding the transformation strategies of green shipyards have been developed.